The Role of the Parasite Life Cycle in Pathogenesis of Infectious Diseases - Trasia, Reqgi First (JURNAL Al-AZHAR INDONESIA SERI SAINS DAN TEKNOLOGI, 2022)
Indonesia is a developing country that has various risk factors that can cause parasitic infections to develop. The role of the life cycle of worms and other parasites has been widely studied before. However, there is still little review of its pathogenesis in Indonesia. The purpose of this article is to examine the role of the parasite life cycle in the pathogenesis of infectious diseases. Based on this review, it can be concluded that Diphyllobothrium latum, Taenia solium, Echinococus granulosus, Hymenolepis nana, Dypilidium caninum, Schistosoma japonicum, Fasciolopsis buski, Heterophyes, Echinostoma, Clonorchis sinensis, Fasciola hepatica, Dicrocoemani, Paragon dencarisius, trichiura, Necator americanus, Ancylostoma duodenale, Stongyloides stercoralis, Trichinela spiralis, Angiostrongylus cantonensis, and Wuchereria bancrofti have different life cycles. This difference will have an impact on the different pathogenesis for each infection. Enforcement and treatment also differ based on the underlying pathogenesis.Keywords – Life Cycle, Parasite, Patogenesis, Infectious disease